The effect of inoculants on silage fermentation properties and on animal production - Meeske, Robin (Stellenbosch : University of Stellenbosch, 2011)
162 leaves printed on single pages, preliminary pages i- vii and numbered pages 1-152. Includes bibliography and abbreviations.